2014
DOI: 10.1002/acn3.83
|View full text |Cite
|
Sign up to set email alerts
|

Plasma profiling reveals three proteins associated to amyotrophic lateral sclerosis

Abstract: ObjectiveAmyotrophic lateral sclerosis (ALS) is the most common adult motor neuron disease leading to muscular paralysis and death within 3–5 years from onset. Currently, there are no reliable and sensitive markers able to substantially shorten the diagnosis delay. The objective of the study was to analyze a large number of proteins in plasma from patients with various clinical phenotypes of ALS in search for novel proteins or protein profiles that could serve as potential indicators of disease.MethodsAffinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Aspartate aminotransferase and aldolase are major targets for deglycation repair by DJ‐1, which is highly induced in many cases of PD (Richarme et al ., 2015). Neurofilament medium polypeptide is one of three plasma proteins strongly associated with ALS (Haggmark et al ., 2014). Cytochrome c oxidase mutations and polymorphisms are associated with multiple neurodegenerative diseases, including AD (Loera‐Castaneda et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Aspartate aminotransferase and aldolase are major targets for deglycation repair by DJ‐1, which is highly induced in many cases of PD (Richarme et al ., 2015). Neurofilament medium polypeptide is one of three plasma proteins strongly associated with ALS (Haggmark et al ., 2014). Cytochrome c oxidase mutations and polymorphisms are associated with multiple neurodegenerative diseases, including AD (Loera‐Castaneda et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…[140]. As one example, light, medium, and heavy chains of neurofilaments have been reported as increased in CSF from MS, ALS, and AD patients, also with concordant levels in serum [31,32,111,141]. Also other common disease markers have been suggested within several neurodegenerative disorders as reviewed by Kroksveen et al [142].…”
Section: Disease Commonalitiesmentioning
confidence: 95%
“…So far, corresponding reports based on plasma analysis have been limited. We addressed this by an extensive plasma profiling study where we identified three proteins, namely neurofilament medium polypeptide (NEFM), regulator of G-protein signaling 18 (RGS18), and mitochondrial carnitine/acylcarnitine carrier protein (SLC25A20) as elevated in plasma from ALS patients [111].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Tissue-elevated proteins could also be searched for and analyzed in serum, for example, using affinity proteomics on suspension bead arrays, as they represent an interesting group of proteins that may be suitable for serumbased diagnostic tests. In a recent study by Haggmark et al [7] focusing on plasma profiling in samples from amyotrophic lateral sclerosis, two out of the three proteins shown to be associated with the disease were tissue-elevated. Serum-based analysis can also be used to discover autoantigens for identification of potential autoimmune targets [8].…”
mentioning
confidence: 99%